Unified analysis of switched diversity systems in independent and correlated fading channels. - Tellambura, C.
The moment generating function (MGF) of the signal power at the output of dual-branch switch-and-stay selection diversity (SSD) combiners is derived. The first-order derivative of the MGF with respect to the switching threshold is also derived. These expressions are obtained for the general case of correlated fading and nonidentical diversity branches, and hold for any common fading distributions (e.g., Rayleigh, Nakagami-m, Rician, Nakagami-q). The MGF yields the performance (bit or symbol error probability) of a broad class of coherent, differentially coherent and noncoherent digital modulation formats with SSD reception. The optimum switching threshold (in a minimum error rate sense) is obtained by solving a nonlinear equation which is formed by using the first-order derivative of the MGF. This nonlinear equation can be simplified for several special cases. For independent and identically distributed diversity branches, the optimal switching threshold in closed form is derived for three generic forms of the conditional error probability. For correlated Rayleigh or Nakagami-m fading with identical branches, the optimal switching threshold in closed form is derived for the noncoherent binary modulation formats. We show previously published results as special cases of our unified expression. Selected numerical examples are presented and discussed
Keywords: Nakagami-m fading; Nakagami-q fading; Rayleigh fading; Rician fading; Bit error probability; Coherent modulation; Correlated fading channels; Differentially coherent digital modulation; Dual-branch switch; Fading distribution; Independent fading channels; Mobile radio; Moment generating function; Noncoherent binary modulation; Noncoherent digital modulation; Nonidentical diversity branches; Selection diversity combiners; Signal power; Switched diversity systems; Switching threshold; Symbol error probability